Self-Regulatory Coping Behaviors and Stress Reactivity: Exploring the Environmental Affordance Model of Health Disparities. (June 2022) - Mezuk, Briana; Kalesnikava, Viktoryia; Spears, Erica; Kirk, Keri; Rafferty, Jane; Del Toro, Juan
Objectives: To explore the relationship between self-regulatory coping behaviors (SRCB) and hypothalamic pituitary adrenal (HPA) stress reactivity. Methods: Data came from the Richmond Stress and Sugar Study (n=125, median age: 57 years, 46% non-Hispanic White, 48% African American). The relationships between 11 SRCB ("health-harming" [e.g., smoking] and "health-promoting" [e.g., exercising]) with HPA stress reactivity, indicated by salivary cortisol response to the Trier Social Stress Test, was assessed using multi-level modeling. Results: Health-harming and health-promoting SRCB were positively correlated (+0.33, p <0.001). Several individual behaviors were related to HPA stress reactivity, for example, smoking and meditation were associated with shallower increases in cortisol (smoking: −13.0%, 95%CI: −20.9% to −4.3%; meditation: −14.0%, 95%CI: −22.0% to −5.1%). However, SRCB summary measures were unrelated to stress reactivity. Discussion: Health-harming and health-promoting SRCB are inter-related. Specific behaviors, rather than groupings as health-harming versus -promoting, are related to HPA stress reactivity.